Spi6 Protects Alloreactive CD4+ But Not CD8+ Memory T Cell From Granzyme B Attack by Double‐Negative T Regulatory Cell. Issue 3 (12th February 2014) - Su, Y.; Jevnikar, A. M.; Huang, X.; Lian, D.; Zhang, Z.‐X.
<x xml:space="preserve">Abstract</x> Memory T (Tm) cells pose a major barrier to long‐term transplant survival. Whether regulatory T cells (Tregs) can control them remains poorly defined. Previously, we established that double‐negative (DN) Tregs suppress effector T (Teff) cells. Here, we demonstrate that DN Tregs effectively suppress CD4+/CD8+ Teff and CD8+ Tm but not CD4+ Tm cells, whereas the suppression on CD8+ Tm is abrogated by perforin (PFN) deficiency in DN Tregs. Consistently, in a BALB/c to B6‐Rag1−/− skin transplantation, transfer of DN Tregs suppressed the rejection mediated by CD4+/CD8+ Teff and CD8+ Tm cells (76.0 ± 4.9, 87.5 ± 5.0 and 63.0 ± 4.7 days, respectively) but not CD4+ Tm cells (25.3 ± 1.4 days). Both CD8+ effector memory T and central memory T compartments significantly reduced after DN Treg transfer. CD4+ Tm highly expresses granzyme B (GzmB) inhibitor serine protease inhibitor‐6 (Spi6). Spi6 deficiency renders CD4+ Tm susceptible to DN Treg suppression. In addition, transfer of WT DN Tregs, but not PFN−/− DN Tregs, inhibited the skin allograft rejection mediated by Spi6−/− CD4+ Tm (75.5 ± 7.9 days). In conclusion, CD4+ and CD8+ Tm cells differentially respond to DN Tregs' suppression. The GzmB resistance conferred by Spi6 in CD4+ Tm cells might hint at the physiological significance of Tm persistence.